Stepwise Regression Analysis of the Determinants Influencing the Adoption of Islamic Banking - Pattanayak, Monalisa; Shankar, A. Udaya; Kumar, Gaurav; Ahmed, S. Fakruddin Ali; Raju, N. S. V. N.; Jeelakarra, Srinivas Ravi Kumar (International Review of Management and Marketing, 2025)
This study explores the key factors influencing the adoption of Islamic Banking (IB) among Pakistani customers. Data were collected from 150 bank customers in the Peshawar district. The analysis involved descriptive statistics and stepwise regression. The findings reveal that religious commitment and consumer perception positively impact IB adoption. Additionally, the study highlights that customers in Pakistan generally have limited knowledge of IB products. These findings are valuable for Islamic banks in refining their marketing strategies. Marketing managers should focus on fostering a positive attitude by increasing awareness and emphasizing the benefits of Islamic banking services. Enhancing service delivery for existing customers can also generate positive word-of-mouth, further encouraging adoption.